2020
DOI: 10.1111/pbi.13382
|View full text |Cite
|
Sign up to set email alerts
|

The strawberry transcription factor FaRAV1 positively regulates anthocyanin accumulation by activation of FaMYB10 and anthocyanin pathway genes

Abstract: The RAV (related to ABI3/viviparous 1) group of transcription factors (TFs) play multifaceted roles in plant development and stress responses. Here, we show that strawberry (Fragaria 9 ananassa) FaRAV1 positively regulates anthocyanin accumulation during fruit ripening via a hierarchy of activation processes. Dual-luciferase assay screening of all fruit-expressed AP2/ ERFs showed FaRAV1 had the highest transcriptional activation of the promoter of FaMYB10, a key activator of anthocyanin biosynthesis. Yeast one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 83 publications
(103 reference statements)
0
66
0
Order By: Relevance
“…In this study, the expression pattern of CitRAV1 transcript accumulation suggested it may also be involved in the process of fruit ripening as well as leaf senescence, which was consistent with previous observations (Woo et al ., 2010). Recently, RAV1 from strawberry was reported to regulate anthocyanin accumulation by directly activating transcription of FaMYB10 and other genes, excluding CHI (Zhang et al ., 2020). In the present study, we showed that although CitRAV1 cannot directly bind to the promoter of CitCHIL1 either, it can form homologous dimers or oligomers and combine with CitERF33 to form transcriptional complexes (Figure 6), which has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression pattern of CitRAV1 transcript accumulation suggested it may also be involved in the process of fruit ripening as well as leaf senescence, which was consistent with previous observations (Woo et al ., 2010). Recently, RAV1 from strawberry was reported to regulate anthocyanin accumulation by directly activating transcription of FaMYB10 and other genes, excluding CHI (Zhang et al ., 2020). In the present study, we showed that although CitRAV1 cannot directly bind to the promoter of CitCHIL1 either, it can form homologous dimers or oligomers and combine with CitERF33 to form transcriptional complexes (Figure 6), which has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…7’ after fading was significantly lower than that in ‘Xinqihong’ at the late coloring stage, which indicates that the expression of PbRAV6 was closely related to the synthesis of anthocyanins. In strawberry ( Fragaria ananassa ), FaRAV1 was shown to promote anthocyanin accumulation by directly binding to the promoter of various genes in the anthocyanin biosynthesis pathway and increasing their expression including FaMYB10 (4.0 fold), chalcone synthase (CHS; 1.53-fold), flavanone hydroxylase (F3H; 1.95-fold), dihydroflavonol 4-reductase (DFR; 3.6-fold), and 5,3-O-glucosyltransferase (GT)1 (2.3-fold) [ 40 ]. In pear, PbRAV6 may have a similar function, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In strawberry, FaMYB9/FaMYB11, FabHLH3, and FaTTG1 from the octoploid Fragaria ananassa form an MBW complex specifically activating proanthocyanidins (Schaart et al, 2013), whereas in a transient assay FvMYB10 and FvbHLH33 from the diploid Fragaria vesca were found to activate the anthocyanin-specific DFR and UFGT promoters (Lin- Wang et al, 2014). Recently, a RAV (related to ABI3/viviparous 1) transcription factor, FaRAV1, has been demonstrated to stimulate anthocyanin accumulation both by up-regulating FaMYB10 and by directly binding to promoters of anthocyanin biosynthetic genes (Zhang et al, 2020a). In pear, an MBW complex has not been identified, but PyMYB114 and PybHLH3 were found to interact with PyERF3 in red pear fruit.…”
Section: Activators and Repressors Of Anthocyanin Biosynthesis In Fruits Vegetables And Other Cerealsmentioning
confidence: 99%